Clinical nurse adherence to professional ethics: A grounded theory. (March 2023) - Yang, Qingqing; Zheng, Zhihui; Pang, Shuqin; Wu, Yilong; Liu, Jujuan; Zhang, Jiahui; Qiu, Xiahua; Huang, Yufeng; Xu, Jia; Xie, Liyue
Background: Professional ethics is the regulation and discipline of nurses' daily nursing work. Nurses often encounter various ethical challenges and problems in their clinical work, but there are few studies on nurses' adherence to professional ethics. Research Aim: An analysis of nursing adherence to nursing ethics from the perspective of clinical nurses in the Chinese public health system. Research Design: This study adopts the grounded theory approach proposed by Strauss and Corbin. Participants and research context: Between July 2021 and January 2022, Clinical nurses were recruited for online video interviews using purposive and theoretical sampling methods in seven hospitals in Beijing, Tianjin, Shanxi, Henan, Guangdong, and Fujian, China. Data analysis was conducted using Strauss and Corbin's coding approach. Ethical considerations: This study was approved by the Ethics Committee of Sanming First Hospital (MingYiLun 71/2021) Findings: A total of 27 participants were included. A theoretical model of nursing staff adherence to professional ethics was constructed. The main core was adherence to professional ethics and the other cores were (1) causal conditions: professional ethics code, individual conscience; (2) intervening conditions: personal growth, social support system, matching career compensation, prediction of adverse consequences; (3) action strategies: sticking to professional values, self-regulation, flexible response, post-event improvement; and (4) outcomes: self-harmony, reduced medical disputes. Conclusions: This study provides an interpretive understanding of why clinical nurses adhere to professional ethics in China and describes the challenges and issues posed by nurses' use of strategies to cope with ethical adversity. The findings can be used to develop future complex studies.